Identifying the needs and problems of the gifted and talented children (2014)
In this study, it has been stressed that just like other children, the gifted children have certain basic needs as well. This includes needs for security, love, belongingness and the need to be accepted as an individual. The gifted children mere seen to have some other specific needs on account of their exceptionality and speciality. Such needs include: the need for the knowledge and understanding, the need for creativity and ingenuity, development of their exceptional ability or abilities, self-actualization or self-expression and the need to feel comfortable with themselves and with the differences that simultaneously open possibilities and create difficulty. In this study, different problems encountered by the gifted and talented children were also discussed. Examples of such problems are: problems arising through the strengths of one's giftedness, problems arising on account of the misdiagnosis and problems arising out of the dual-exceptionality. Effort was also mode to highlight the need to nurture the gifts and talents of children. Finally, ways to help the perfectionistic child and to nurture giftedness in a child were extensively enumerated.